Risk of Adverse Events in Cancer Patients Receiving Nivolumab With Ipilimumab: A Meta-Analysis - Zhao, Xin; Gao, Fengwei; Yang, Jie; Fan, Hua; Xie, Qingyun; Jiang, Kangyi; Gong, Jie; Gao, Benjian; Yang, Qian; Lei, Zehua (Frontiers in Oncology, 2022)
Background: Combining two immune checkpoint inhibitors (ICIs) instead of using one can effectively improve the prognosis of advanced malignant tumors. At present, ipilimumab alongside nivolumab is the most widely used combinatorial regimen of ICIs. However, the risk of treatment-related adverse events is higher in combinatorial regimens than in single-drug regimens. Thus, this study aimed to evaluate the risks of common adverse events associated with the combinatorial regimen of ipilimumab and nivolumab by using meta-analysis. Methods: We searched Pubmed, Medline, EMBASE, and Cochrane Library for reports published by 30 September 2021. A randomized controlled study was developed and analyzed using the statistical software R to determine the efficacy of the combinatorial treatment. Risk estimates (hazard ratios, RR) and 95% confidence intervals for various common serious adverse events were used. Results: A total of 23 randomized control trials (n = 3970 patients) were included. Our meta-analysis indicated the risks of adverse events of any grade and grade ≥ 3 as 90.42% (95%CI, 85.91%~94.18%) and 46.46% (95%CI, 39.37%~53.69%), respectively; the risks of treatment-related death and adverse events leading to discontinuation were estimated at 0.42% (95% CI, 0.18%~0.72%) and 19.11% (95% CI, 14.99%~24.38%), respectively. Classification of 19 common adverse events. The top 5 grade 1–2 adverse events were found to be fatigue(30.92% , 95% CI: 24.59%~37.62%,), pruritus(26.05%, 95%CI: 22.29%~29.99%), diarrhea(23.58%, 95% CI: 20.62%~26.96%), rash(19.90%, 95%CI: 15.75%~25.15%), and nausea(17.19%, 95% CI: 13.7%~21.57%). The top 5 grade ≥ 3 adverse events were identified as increased alanine aminotransferase(8.12%, 95% CI: 5.90%~10.65%), increased lipase(7.62%, 95% CI: 4.88%~10.89%), and colitis (6.39%, 95%CI: 3.98%~10.25%), increased aspartate aminotransferase (6.30%, 95% CI: 4.61% ~ 8.22%), and diarrhea(5.72%, 95%CI: 3.50% ~ 8.44%). Subgroup analysis revealed differences between the N1–I3 and N3–I1 subgroups in the risks of common adverse events of any grade and ≥ grade 3 and in the type of the event. Conclusion: This study summarized the risks of common adverse events in the co-treatment of malignant-tumor patients with ipilimumab and nivolumab and identified the impacts of various initial administration schemes on the risks of such events, thereby providing an important reference for the toxicity of co-treatment with ipilimumab and nivolumab.